Quality of life for caregivers of a child aged 6-16 years with Autistic Spectrum Disorder and/or an intellectual disability : a comparative study : a thesis presented in fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Turitea, New Zealand - Browne, Natasha Jane; Browne, Natasha Jane (Massey University, 2010)
Quality of life for caregivers of children with autistic spectrum disorder and/or an intellectual disability was compared to quality of life for those caring for a normally developing child. Participants were caregivers of children between 6 - 16 years of age who were divided into two groups: Caregivers of disabled children (Group 1, n = 60) and caregivers of normally developing children (Group 2, n = 13). The research investigated differences of overall quality of life between groups. Within Group One the influence on quality of life for caregivers was investigated in relation to the child's behaviour, level of support the child requires to complete activities of daily living, caregivers marital status, caregivers socio-economic level, and caregivers satisfaction with perceived supports. The Quality of Life Index and the Nisonger Child Behavior Rating Form were used to determine quality of life and problem behaviours. Results showed a difference in overall quality of life between groups. Child's behaviour was found to have a significant relationship with caregiver‘s quality of life. Satisfaction with perceived supports had a weak relationship to caregiver‘s quality of life. No statistically significant relationship was found between caregiver‘s quality of life and the child's activities of daily living requirements, caregiver‘s marital status or caregiver‘s socio-economic status. Quality of life for caregivers of developmentally disabled children was shown to be lower than the general population. New Zealand is currently in a state of flux in regards to addressing and refining disability support services. Research that further investigates these results may enhance service delivery and result in better outcomes for those supporting children with a disability.
Keywords: Autism; Caregivers' wellbeing; Quality of life; Behavioural problems; Autistic children